Comparison of Conventional Alkaline Nasal Douching with Budesonide Nasal Irrigation on Post Endoscopic Sinus Surgery Patients (Journal of Nobel Medical College, 2025)
Background: Postoperative care after endoscopic sinus surgery for chronic rhinosinusitis plays a vital role in enhancing mucosal healing and preventing recurrence. This study aimed to compare the effectiveness of conventional alkaline nasal douching with budesonide nasal irrigation in patients undergone endoscopic sinus surgery.Materials and Methods: This prospective comparative study was conducted at the Department of Ear, Nose and Throat and Head and Neck Surgery at the Manipal Teaching Hospital. A total of 80 patients with chronic rhinosinusitis with or without nasal polyps who underwent ESS were randomly assigned into two groups: Group A (alkaline nasal douche) and Group B (budesonide nasal irrigation) following same regimen of antibiotics, nasal steroids, analgesics and antihistamines. Data were collected from the outpatient department at the time of follow-up on 2, 6, and 10 weeks postoperatively as per the endoscopic Lund-Kennedy scoring system.Results: Budesonide nasal irrigation was significantly more effective in reducing postoperative nasal polyps, edema and scarring as compared to the alkaline nasal irrigation group, particularly at 6 and 10 weeks (p